Coordination and Team work Depth analysis of Employee Performance at PT. XYZ - Dulmukmin; Elly Herawatye (International Journal of Management, Economic, Business and Accounting, 2022)
This study aims to examine the effect of Coordination, Human Resource Development and Teamwork on Employee Performance at PT XYZ. To test these variables, researchers used employees of PT. XYZ as the object of research. The research was conducted using a survey method by distributing questionnaires to 93 employees at PT. XYZ In this study the author uses a quantitative The results of research on Coordination, Human Resource Development, and Teamwork indicate that it positively affects employee performance, which can be interpreted as the better/higher Coordination, Human Resource Development and Teamwork, the better/higher the performance of the company's employees